Effets des transferts des migrants sur l’investissement productif au Sénégal - Marieme Coulibaly, (Revue Internationale de la Recherche Scientifique (Revue-IRS), 2025)
This article is a microeconomic analysis of the impact of migrant remittances on productive investment. Statistical analyses and econometric estimations demonstrate the existence of a positive relationship between migrant remittances and productive investment in Senegal.